Screening for Severe Acute Respiratory Syndrome Coronavirus 2 in Close Contacts of Individuals With Confirmed Infection: Performance and Operational Considerations. (20th May 2022) - Zobrist, Stephanie; Oliveira-Silva, Michelle; Vieira, Alexia Martines; Bansil, Pooja; Gerth-Guyette, Emily; Leader, Brandon T; Golden, Allison; Slater, Hannah; Cruz, Catherine Duran de Lucena; Garbin, Eduardo; Sagalovsky, Mariana; Pal, Sampa; et al.
Abstract: Background: Point-of-care and decentralized testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is critical to inform public health responses. Performance evaluations in priority use cases such as contact tracing can highlight trade-offs in test selection and testing strategies. Methods: A prospective diagnostic accuracy study was conducted among close contacts of coronavirus disease 2019 (COVID-19) cases in Brazil. Two anterior nares swabs (ANS), a nasopharyngeal swab (NPS), and saliva were collected at all visits. Vaccination history and symptoms were assessed. Household contacts were followed longitudinally. Three rapid antigen tests and 1 molecular method were evaluated for usability and performance against reference reverse-transcription polymerase chain reaction (RT-PCR) on nasopharyngeal swab specimens. Results: Fifty index cases and 214 contacts (64 household) were enrolled. Sixty-five contacts were RT-PCR positive during ≥1 visit. Vaccination did not influence viral load. Gamma variants were most prevalent; Delta variants emerged increasingly during implementation. The overall sensitivity of evaluated tests ranged from 33% to 76%. Performance was higher among symptomatic cases and those with cycle threshold (Ct) values <34 and lower among oligosymptomatic or asymptomatic cases. Assuming a 24-hour time to results for RT-PCR, the cumulative sensitivity of an anterior nares swab rapid antigen test was >70% and almost 90% after 4 days. Conclusions: The near-immediate time to results for antigen tests significantly offsets lower analytical sensitivity in settings where RT-PCR results are delayed or unavailable. Abstract : This study evaluated the performance of 3 rapid antigen tests and 1 molecular method for detecting severe acute respiratory syndrome coronavirus 2 among close contacts of coronavirus disease 2019 case patients and found that near-immediate time to results for antigen tests significantly offsets lower sensitivity when polymerase chain reaction results are delayed or unavailable.